Statistical and Prognostic Modeling of Clinical Outcomes with Complex Physiologic Data - Puertas Vásquez, Mónica Aurora (2014)
Descargue el texto completo en el repositorio institucional de la University of South Florida: https://scholarcommons.usf.edu/etd/5106